Legionnaires’ Disease Complicated with Rhabdomyolysis and Acute Kidney Injury in an AIDS Patient - Karan Seegobin; Satish Maharaj; Cherisse Baldeo; Julio Perez Downes; Pramod Reddy (Case Reports in Infectious Diseases)
Objective. To present a case of an uncommon triad of Legionella pneumonia, rhabdomyolysis, and renal failure, with review of the relevant literature. Case. A 51-year-old with a history of human immunodeficiency virus (HIV), chronic obstructive pulmonary disease (COPD), and hypertension presented with fever, cough, and shortness of breath over four days. Chest X-ray showed consolidation in left lower lung field; urine was positive for Legionella antigen and myoglobin; creatine kinase was 51092U/L; creatine was 6.9 mg/dL, and his CD4 count was 41 cells/ul. He was managed with azithromycin and levofloxacin and further required dialysis and ventilatory support in the intensive care unit due to renal failure and respiratory failure. He responded well to the treatment and made a complete recovery. Legionella pneumophila infection is a recognized but rare cause of rhabdomyolysis with high morbidity and mortality when there is extrapulmonary involvement. Early diagnosis and appropriate treatment is essential to improve outcomes. Conclusion. Physicians should consider Legionella pneumonia in patients with rhabdomyolysis, renal failure, and respiratory symptoms. Early diagnosis and treatment have been shown to have good clinical response. Timely intensive care management, together with early and judicious use of dialysis in patients complicated with rhabdomyolysis and renal failure, may lead to good outcomes.